Pengembangan Media Pembelajaran Berbasis Canva untuk Meningkatkan Hasil Belajar Siswa - Dermawani Ziliwu; Suryanti Novita lase; Pilih Eli Lase; Imansudi Zega (Departement of Mathematics Education, 2023)
To enhance student learning results, this study makes use of Canva-based instructional materials. This study aims to ascertain how SMP Negeri 1 Botomuzoi students react to canva-based learning materials and the viability of such materials. Research and development (R&D) is the methodology employed in this study, and the model used is ADDIE. A questionnaire used for data collection in this study was approved by linguists, media specialists, and material experts. The results of validation received from material specialists showed that 85% of them indicated very valid, 87.5% of them indicated extremely valid, and 85% of linguists indicated very valid. 92% of students scored extremely well on the student response form, though.